Raffaele D’Amato and Andrea Salimbeti. Early Iron Age Greek Warrior 1100–700 BC. - Dickinson, Oliver (Journal of Greek Archaeology, 2018)
This is the third booklet in this format concerned with ‘warriors’ of Greece by the same authors, the others being Early Aegean Warrior 5000–1450 BC (2013) and Bronze Age Greek Warrior 1600–1100 BC (2011). All include among their illustrations many colourful reconstructions by Giuseppe Rava, which considerably enhance the quality of these booklets by their imaginative if often over-enthusiastic liveliness.